Layered approach in energy-efficient Information Technology (IT) classroom design - Nurika, Okta; Hanafi, Hafizul Fahri; Tang Jung, Low; Abba Haruna, Ahmed (Journal of ICT in Education, 2024)
Designing an energy-efficient IT classroom has not been straightforward due to the scattered recommended practices that involve different aspects. Some related aspects have not even been explored and need to be included - to increase the level of power saving and flexibility in implementation. Thus, a comprehensive layered approach or method is designed by this paper. It involves four (4) layers that represent different aspects of an IT classroom that can be made efficient in terms of energy consumption, namely hardware, platform, middleware, and application layers. Each layer is autonomous and hence can be implemented flexibly, subject to the bespoke feasibility of the use case. The proposed method is also expected to be future-proof and expandable due to its catering to both hardware and software-based optimizations. Such guidance is also crucial for the ongoing Industrial Revolution (IR) 4.0 and soon-to-be-established IR 5.0, where smart cities worldwide would be required to be energy-efficient.